Protective effects of melatonin against physical injuries to testicular tissue: A systematic review and meta-analysis of animal models - Dehdari Ebrahimi, Niloofar; Shojaei-Zarghani, Sara; Taherifard, Ehsan; Dastghaib, Sanaz; Parsa, Shima; Mohammadi, Nasim; Sabet Sarvestani, Fatemeh; Moayedfard, Zahra; Hosseini, Nima; Safarpour, Heidar; Sadeghi, Alireza; Azarpira, Negar; et al. (Frontiers in Endocrinology, 2023)
Background Modern societies face infertility as a global challenge. There are certain environmental conditions and disorders that damage testicular tissue and may cause male infertility. Melatonin, as a potential antioxidant, may protect testicular tissue. Therefore, we conducted this systematic review and meta-analysis to evaluate the effects of melatonin in animal models against physical, heat, and ischemic damage to the testicular tissue. Methods PubMed, Scopus, and Web of Science were systematically searched to identify animal trials evaluating the protective effect of melatonin therapy on rodent testicular tissue when it is exposed to physical, thermal, or ischemic stress. Random-effect modeling was used to estimate the standardized mean difference and 95% confidence intervals based on the pooled data. Additionally, the Systematic Review Centre for Laboratory Animal Experimentation (SYRCLE) tool was used to assess the risk of bias. The study protocol was prospectively registered in PROSPERO (CRD42022354599). Results A total of 41 studies were eligible for review out of 10039 records. The histopathological characteristics of testicular tissue were generally improved in rodents by melatonin therapy. Based on the pooled data, sperm count, morphology, forward motility, viability, Johnsen's biopsy score, testicular tissue glutathione peroxidase, and superoxide dismutase levels were higher in the melatonin treatment rodent arms. In contrast, the malondialdehyde level in testicular tissue was lower in the treatment rodent arms. The included studies suffered from a high risk of bias in most of the SYRCLE domains. Conclusion This study concludes that melatonin therapy was associated with improved testicular histopathological characteristics, reproductive hormonal panel, and tissue markers of oxidative stress in male rodents with physical, ischemic, and thermal testicular injuries. In this regard, melatonin deserves scientific investigations as a potential protective drug against rodent male infertility.